Efficacy of palifermin on oral mucositis and acute GVHD after hematopoietic stem cell transplantation (HSCT) in hematology malignancy patients: a meta-analysis of trials - Hamid Reza Mozaffari; Mehrdad Payandeh; Mazaher Ramezani; Masoud Sadeghi; Mohammad Mahmoudiahmadabadi; Roohollah Sharifi (Contemporary Oncology)
Aim of the study : Herein, this meta-analysis study evaluated the efficacy of palifermin after HSCT on the incidence and severity of OM or aGVHD in hematologic malignancy patients in randomized clinical trials (RCTs). Materials and methods : To compare the efficacy of palifermin on adverse events, OM and aGVHD compared with placebo , we searched databases of PubMed/Medline, Web of Science and Cochrane Library for RCTs based on a number of criteria. Results : There was no difference observed in the incidence of OM and aGVHD between two groups. The subgroup analysis didn’t show significant differences in two groups for aGVHD grade 2–4 (odds ratio [OR] = 1.54, 95% confidence interval (CI): 0.70–3.39, p = 0.28), aGVHD grade 3–4 (OR = 0.97, 95% CI: 0.48–1.94, p = 0.92), OM grade 2–4 (OR = 0.76, 95% CI: 0.42–1.38, p = 0.37) and OM grade 3–4 (OR = 0.54, 95% CI: 0.25–1.15, p = 0.11], but erythema as an adverse effect in palifermin group was higher than placebo group (OR = 1.86, 95% CI: 1.10–3.15, p = 0.02]. Conclusions : This meta-analysis of six clinical trials found no statistically significant difference in OM and aGVHD grades in patients receiving 60 µg/kg/day dose of palifermin compared with those receiving a placebo . However, oral mucosal erythema was more prevalent among patients receiving palifermin than patients receiving a placebo .